The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/21691401.2018.1452020
|View full text |Cite
|
Sign up to set email alerts
|

Nano vanadium dioxide films deposited on biomedical titanium: a novel approach for simultaneously enhanced osteogenic and antibacterial effects

Abstract: Vanadium is a trace element in the human body, and vanadium compounds have a promising future in biological and medical applications due to their various biological activities and low toxicity. Herein, a novel pure vanadium dioxide (VO) nanofilm was deposited on a substrate of biomedical titanium by magnetron sputtering. The antibacterial effect of VO against the methicillin-resistant Staphylococcus aureus (MRSA) was validated in vitro and in vivo. Moreover, the biocompatibility of VO and its osteogenic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Nano vanadium dioxide (VO 2 ) deposited on biomedical titanium demonstrated osteogenic activity in rat mesenchymal stem cells by regulating ROS levels [82].…”
Section: Anticancer Potencymentioning
confidence: 99%
“…Nano vanadium dioxide (VO 2 ) deposited on biomedical titanium demonstrated osteogenic activity in rat mesenchymal stem cells by regulating ROS levels [82].…”
Section: Anticancer Potencymentioning
confidence: 99%
“…107 It was reported that the anti-MRSA activity of vancomycin pH-responsive lipid nanoparticles was 1.8-fold higher than vancomycin in vivo. 108 In addition, some inorganic materials with good biologic activities and low toxicity (vanadium dioxide) 109 also showed satisfactory effects on S. aureus infections in vivo. For example, the silica nanoprobe coated with vancomycin and decorated with polyelectrolyte-cypate complexes can selectively enable rapid (4 hours postinjection) near infrared fluorescence imaging with high sensitivity (10 5 colony-forming units) and achieve efficient photothermal therapy of MRSA infections in mice.…”
Section: Enhanced Therapeutic Efficiency In Vivomentioning
confidence: 99%
“…Vanadium dioxide with monoclinic structure, VO 2 (M), is the only material that possesses a reversible metal-to-semiconductor transition (MST) the nearest to the room temperature with the critical temperature at 68 ○ C. 6 The electrical and optical properties are also changing in accordance to this transformation. All this phenomenon is essential for the application of smart window, switching device, 7,8 thermal imaging, 9 hydrogen storage, 10,11 Lithium-ion batteries, 12 antioxidants, 13,14 and the combination composites of VO 2 (M) with other materials to be used as multifunctional materials. [15][16][17][18] Vanadium dioxide has been manufactured as nanoparticle as well as thin films using various chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%